2020
DOI: 10.1007/s11419-020-00523-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative neuropharmacological studies on three pyrrolidine-containing synthetic cathinones

Abstract: Purpose 3,4-Methylenedioxypyrovalerone (3,4-MDPV) is a prevalent member of α-pyrrolidinophenones, a group of new psychoactive substances, known for its strong psychostimulant effect resulting from potent stimulation of dopamine (DA) circuitry in the brain. As 3,4-MDPV and its derivatives are successively being scheduled, each year novel analogs appear on the market. This study aimed at examination and direct comparison of psychostimulant properties of structural isomer of 3,4-MDPV, namely 2,3-MDPV along with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Animal head-dipping behavior remains closely correlated with their psychological response. Gamma amino-butyric acid (GABA) can modulate the central nervous system through the voltage-gated Ca 2+ channel or chlorine conductance [40][41][42][43][44][45][46][47][48][49][50]. It was revealed that the animals' head-dipping behavior is clearly relevant to their mental state, and this test is used to investigate anxiety-related activities.…”
Section: Discussionmentioning
confidence: 99%
“…Animal head-dipping behavior remains closely correlated with their psychological response. Gamma amino-butyric acid (GABA) can modulate the central nervous system through the voltage-gated Ca 2+ channel or chlorine conductance [40][41][42][43][44][45][46][47][48][49][50]. It was revealed that the animals' head-dipping behavior is clearly relevant to their mental state, and this test is used to investigate anxiety-related activities.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, for example, there have been a particularly high number of deaths due to opioid overdoses in recent years (91). These substances cause a euphoric effect as they bind to the presynaptic µ-opioid receptors (83). One of the main symptoms in the case reports studied was impaired thinking and a decreased level of consciousness.…”
Section: (Continued)mentioning
confidence: 96%
“…The obtained results indicate a greater influence of synthetic cathinone intake on the occurrence of aggression in comparison to cannabinoids. The presence of a pyrrolidine ring and a quaternary amine moiety increases the lipophilicity and potency of these compounds (83). An example of this is MDPV, the consumption of which has been reported to cause fatalities as well as extremely aggressive behavior (84).…”
Section: (Continued)mentioning
confidence: 99%
“…In vitro affinity studies indicate that pyrovalerones should not interact with SERT and should not cause 5‐HT release, therefore the observed elevated 5‐HT concentration can presumably be explained by the functional coupling of dopaminergic and serotonergic systems. In the case of high extracellular DA concentrations, the phenomenon of its uptake by SERT is observed, accompanied by a concomitant SERT‐mediated release of 5‐HT (Larsen et al., 2011; Simmler, 2018; Wojcieszak Andrzejczak et al., 2020; Wojcieszak et al., 2018). Interestingly, recent studies in mice have shown that SCs possessing a pyrrolidine ring, unlike SCs of the second methamphetamine‐like group, cause, in addition to horizontal, also vertical increased dose‐dependent locomotor activity.…”
Section: Neuropharmacological Profiles Of Synthetic Cathinonesmentioning
confidence: 99%
“…Interestingly, recent studies in mice have shown that SCs possessing a pyrrolidine ring, unlike SCs of the second methamphetamine‐like group, cause, in addition to horizontal, also vertical increased dose‐dependent locomotor activity. The increased vertical locomotor activity is presumably indicative of particularly potent and selective dopaminergic stimulation and anxiety reduction in contrast to derivatives such as those of the second methamphetamine‐like group (Wojcieszak, Andrzejczak, et al., 2020; Wojcieszak et al., 2018, 2019; Wojcieszak, Kuczyńska, & Zawilska, 2020). Popular compounds in this group include, among others, PV8 (1‐Phenyl‐2‐pyrrolidin‐1‐ylheptan‐1‐one), MDPV, and α‐PVP (1‐phenyl‐2‐[1‐pyrrolidinyl]‐1‐pentanone) (Simmler, 2018; Simmler et al., 2013).…”
Section: Neuropharmacological Profiles Of Synthetic Cathinonesmentioning
confidence: 99%